2001
DOI: 10.1002/ijc.1574
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heavy subunit of γ‐glutamylcysteine synthetase (γ‐GCSh) in human colorectal carcinoma

Abstract: Gamma-glutamylcysteine synthetase (␥-GCS) is a heterodimer consisting of heavy (␥-GCSh) and light (␥-GCSl) subunits. ␥-GCS catalyzes the rate-limiting de novo biosynthesis of glutathione (GSH), an abundant physiological antioxidant that plays important roles for regulating oxidative stress. Expression of ␥-GCSh and ␥-GCSl are sensitive to oxidative stress. To investigate whether expression of ␥-GCS is correlated with tumor progression, we used immunohistochemical approaches to examine 16 human colorectal adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…41 Indeed, frequent coexpression patterns of mRNAs for MRP1, g-GCS heavy subunit (g-GCSh) and GSTp were reported in a number of drug-resistant cell lines as well as human cancers. 42,43 It is suggested that the components of MRP1/GS-X pump can be coinduced by many cytotoxic agents. 44,45 Furthermore, it has been suggested that c-jun/AP-1 may be implicated in the regulation of expression of g-GCSh and GSTp 45,46 Collectively, in this study, g-GCSh and GSTp might be also induced by DOX via the JNKmediated pathway, leading to the increase in MRP1-mediated efflux.…”
Section: Discussionmentioning
confidence: 99%
“…41 Indeed, frequent coexpression patterns of mRNAs for MRP1, g-GCS heavy subunit (g-GCSh) and GSTp were reported in a number of drug-resistant cell lines as well as human cancers. 42,43 It is suggested that the components of MRP1/GS-X pump can be coinduced by many cytotoxic agents. 44,45 Furthermore, it has been suggested that c-jun/AP-1 may be implicated in the regulation of expression of g-GCSh and GSTp 45,46 Collectively, in this study, g-GCSh and GSTp might be also induced by DOX via the JNKmediated pathway, leading to the increase in MRP1-mediated efflux.…”
Section: Discussionmentioning
confidence: 99%
“…68 Previous studies indicated that the cystine transport system X c 2 is involved in upregulation of intracellular GSH levels and drug resistance in ovarian cancer cell lines. 69 g-GCS has been reported to be upregulated in numerous cancers, including prostate cancer, 70 multiple myeloma, 71 nonsmall cell lung carcinoma, 72 colorectal carcinoma 73 and mesothelioma. 74 In the present study, no changes in expression levels of the catalytic subunit of this enzyme were observed during carcinogenesis (data not shown); however, activity levels were not measured.…”
Section: Discussionmentioning
confidence: 99%
“…In human colorectal carcinomas, strong cytoplasmic staining for GCS heavy subunit was detected with a higher frequency than in adenoma and was significantly correlated with multidrug-resistance protein 1 expression (197). Another GSH-related enzyme, glutathione-S-transferase (GST), was elevated in colonic neoplasia compared with adjacent normal mucosa (129), but only a marginal increase in breast cancer was noted compared with normal adjacent tissues (44).…”
Section: Gsh Gsh-related Enzymes In Cancer Cellsmentioning
confidence: 99%